Women Editing Modernism : "Little" Magazines and Literary History - Marek, Jayne E., 1954- (Book collections on Project MUSE., 2015)
For many years young writers experimenting with forms and aesthetics in the early decades of this century, small journals known collectively as ""little"" magazines were the key to recognition. Joyce, Stein, Eliot, Pound, Hemingway, and scores of other iconoclastic writers now considered central to modernism received little encouragement from the established publishers. It was the avant-garde magazines, many of them headed by women, that fostered new talent and found a readership for it. Jayne Marek examines the work of seven women editors -- Harriet Monroe, Alice Corbin Henderson, Margaret An.